2007
DOI: 10.1021/cm070950k
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineered Catalyst Particles as a Key for Tailor-Made Carbon Nanotubes

Abstract: Independent control of density and diameter of carbon nanotubes (CNT) is achieved by catalytic growth from iron nanoparticles pre-defined by inert gas condensation. This two-stage process offers the opportunity to investigate the particles prior to the CNT growth, thereby providing deeper insight into the growth mechanisms. The intimate correlation between particle and CNT diameters at particle densities, where interparticle coalescence is unavoidable, points to the nucleation of CNT setting in prior to this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 27 publications
5
43
0
Order By: Relevance
“…The catalyst particles, as with all experiments in this study, were deposited via a gas phase deposition route. 18 Figure 4. The micrograph shows an elongated catalyst particle (Co in this case) residing on the edge of an ␣-Al 2 O 3 platelet (support).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst particles, as with all experiments in this study, were deposited via a gas phase deposition route. 18 Figure 4. The micrograph shows an elongated catalyst particle (Co in this case) residing on the edge of an ␣-Al 2 O 3 platelet (support).…”
Section: Resultsmentioning
confidence: 99%
“…Fe or Co targets in an Ar and/or He atmosphere were used. 18 The catalyst particles were deposited onto thermally oxidized silicon substrates with 10 nm Al 2 O 3 surface layers or 100 nm TiN layers (Samsung), high purity graphite (Goodfellows) or ␣-alumina nanoplatelets. To obtain a priori information on the deposited catalyst particles, they were simultaneously deposited onto carbon-coated transmission electron microscopy (TEM) grids which served as witness plates.…”
Section: Methodsmentioning
confidence: 99%
“…During transfer of a particle sample from the particle deposition chamber into a microscope or into the CVD reactor, the particles were exposed to ambient air and may be oxidized. Further experimental details can be found elsewhere [34,35] and in the ESM. Low voltage HRTEM was carried out using an FEI Titan 3 microscope with third-order spherical aberration correction, operating at an accelerating voltage of 80 kV (i.e., below the knock-on damage threshold for graphite).…”
Section: Methodsmentioning
confidence: 99%
“…However, we found that RF magnetron sputtering is a better method to deposit the nanoparticle catalyst, producing a homogeneous distribution of the catalyst with the possibility to control the size and distribution of the nanoparticles. [ 32 ] Raman spectra measured before and after the sputtering showed that the sputtering does not compromise the integrity of the graphene, as shown in Figure S5, Supporting Information.…”
Section: Communicationmentioning
confidence: 96%
“…At areas of low Ni density, the etching lines are not enough to produce GNRs (Figure 3 a), while at high-density areas, misalignment of the etching lines occurs (Figure 3 c). At these areas, larger nanoparticles are produced owing to coalescence of smaller ones, [ 18,32 ] as evidenced by the gradual increase of the etching width as the particle gets bigger during its movement. Etching by those large particles is not always parallel to the [11 01] sapphire direction.…”
Section: Communicationmentioning
confidence: 99%